Cayley graphs on nilpotent groups with cyclic commutator subgroup are hamiltonian - Ghaderpour, Ebrahim (Ars mathematica contemporanea, 2014)
We show that if ?$G$? is any nilpotent, finite group, and the commutator subgroup of ?$G$? is cyclic, then every connected Cayley graph on ?$G$? has a hamiltonian cycle.
Keywords: Cayley graph; commutator subgroup; graph theory; grupe; hamiltonian cycle; nilpotent group; teorija grafov